Effects of Heterogeneous Environment After Deforestation on Plant Phenotypic Plasticity of Three Shrubs Based on Leaf Traits and Biomass Allocation - Wang, Jinniu; Gao, Jing; Wu, Yan; Xu, Bo; Shi, Fusun; Zhou, Haiyan; Bisht, Neha; Wu, Ning (Frontiers in Ecology and Evolution, 2021)
Responses of plants to heterogeneous environment in the natural world are species-specific, and also depend on their life forms, development stages as well as the various types of environmental factors. This study aimed to understand phenotypic plasticity and ecological adaptability of three shrubs (Salix etosia, Rubus setchuenensis, and Hydrangea aspera) with unique life forms integrated affected by associated potential variables after deforestation. Soil organic carbon content, total nitrogen content, and available nitrogen content were greater outside the forests than those inside the forests, but other factors measured were in contrast. For leaf traits and stoichiometric indicators, there were significant interactions of leaf area (LA),leaf dry matter (DW), specific leaf area(SLA) and leaf phosphorus content (LPC) between shrub species and heterogeneous environments (P<0.05) but not for leaf C/N, N/P, and C/P of all three shrub species between outside- and inside the forests(P>0.05). Principle components analysis (PCA) indicated that soil temperature, pH value, soil carbon content, soil nitrogen content, and MBC and MBN were mainly consisting of the first, given species-specific variations and compositions existed for three shrubs. Summarized results indicated that TB and leaf C/P of S. etosia were significantly correlated with three principal components but only marginal significant correlations exited between R/S and relevant components. SLA and R/S of R. setchuenensis just had marginal significant relationships with independent variables. Both SLA and TB of H.aspera were significantly correlated with three principal components. Based on the pooled values of leaf functional traits and leaf stoichiometric indicators, R. setchuenensis (vining type) had better leaf traits plasticity to adapt heterogeneous environment. In descending order, the ranks of biomass allocation plasticity index of three shrubs were H. aspera (bunch type), R. setchuenensis (vining type), and S. etosia (erect type). Regarding integrated plasticity values of leaf traits and biomass allocation, H. aspera (bunch type) reached the first place of total plasticity and was close to R. setchuenensis, and tailed by S. etosia with less adaptive plasticity in heterogeneous environments.